Dungun district resource analysis : introduction - Long, Ahmad (UTM, 2008)
The intension of the study is to investigate and identified the current condition, issues and potential of Dungun District socio-economic and physical resources. This study also to look in like of the current local, regional and national development policies and strategies which include RSN, RFN, RTD and ECER. Following that, this report will present the finding and recommendation base on from the analysis of the various sectors, which will be the base for the preparation of development proposal.